The Effect of Resting Heart Rate on the New Onset of Microalbuminuria in Patients With Type 2 Diabetes: A Subanalysis of the ROADMAP Study - Schmieder, Roland; Bramlage, Peter; Haller, Hermann; Ruilope, Luis M.; Boehm, Michael (Medicine, 2016)
The association between resting heart rate and new-onset microalbuminuria in patients with type 2 diabetes is not clear. The objective of the current analysis was to assess the relationship between heart rate and incidence of microalbuminuria in patients with type 2 diabetes.Data from the Randomised Olmesartan and Diabetes Microalbuminuria Prevention (ROADMAP) study were retrospectively analyzed. New-onset microalbuminuria was documented and related to heart rate as recorded at baseline and last assessment, and the mean of the measurements taken during the double-blind part of the ROADMAP trial.Patients (n = 4299) had a mean age of 57.8 ± 8.7 years and 46.3% were male. Characteristics were not different between the olmesartan and the placebo groups, except for a higher systolic blood pressure (136.7 vs 135.7 mm Hg; P = 0.04) and albumin creatinine ratio (5.9 vs 5.5; P = 0.03).Increased risk of microalbuminuria was found with increasing heart rate, independent of whether baseline [highest vs lowest quartile odds ratio (OR) 1.39; 95% confidence interval (95% CI) 1.03-1.87; P = 0.032], last assessment (OR 1.71; 95% CI 1.26-2.31; P = 0.001), or mean heart rate was considered (OR: 1.77; 95% CI: 1.30-2.41; P = 0.0003). The greater risk of new-onset microalbuminuria with a high baseline heart rate was also found when data were adjusted for mean systolic blood pressure (OR: 1.35; 95% CI: 1.00-1.82; P = 0.0496; interaction P < 0.0001). Although there was no risk increase with baseline heart rate in the placebo group (P = 0.8253 for trend), microalbuminuria was less frequent in patients receiving olmesartan in the low heart rate quartiles (P = 0.002 for trend).A low heart rate reduces the risk of patients with type 2 diabetes developing microalbuminuria, independent of blood pressure. The data demonstrate potential benefits of reducing the heart rate of type 2 diabetes patients, and indicate that olmesartan could, in particular, reduce the risk of microalbuminuria in patients with low heart rate.
EVALuna2:3855